Assessment of Pattern of Suicidal, Accidental and Homicidal Cases Along with the Sort of Poisoning in North Indian Population (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: This study aims at determining the mode of suicidal, accidental and homicidal cases alongwith the sort of poisoning in north Indian population in relation to age, gender, profession, marital status,upshot of diverse cases of poisons and prerequisite of ventilatory support in dissimilar kind of poisonings.Materials and Methods: The study includes patients who had been earlier exposed to the to poison eitherby domestic or farming pesticide, snakebite, toxic plants, stings, manufacturing pollutant, drugs or variedstuffs. The status of patients undergone through poisoning regardless of age, gender, sort as well as methodof poisoning, constituent of poisons were recorded in a proforma as prescribed by WHO guidelines .Results: Poisoning was more during summer season was found to be having the majority of cases which comprised35.0% of the total recorded incidents. Household and agricultural agents comprising of the 55.2% of thetotal were followed by bites and stings comprising 26.2% were allied with a large amount of poisoning. Conclusion: The prototype of poisoning in the current study is no exception with the patterns observedin most of the other associated studies, preponderance of fatalities comprised male and toxins used foragriculture affairs.